(untitled) (Current Horticulture, 2024)
An experiment was conducted to evaluate the effect of growing environment on graft compatibility and its success in cucurbits, at Kittur Rani Channamma College of Horticulture, Arabhavi, Belagavi district, Karnataka, during kharif 2018-19 and rabi 2019-20 seasons. Among both growing environments, (open field and shade net condition), field transplanted grafted plants did not survive 20 days after grafting, hence the study was continued to know the performance of grafted plants under shade net condition. Graft compatibility and its success was significantly influenced by different cucurbitaceous rootstocks and scions. Significant and maximum graft success (89.33 and 96.33 %), maximum vine length (227.30 and 269.91cm 40 DAG), minimum number of days to first and 50 % sprouting, final girth of graft union (16.36, 20.04, 13.37, 16.39 at 60 & 90 DAG), node number to first female flower appearance (19.14, 8.28) and days to first female flower appearance (33.15, 45.62) were noticed in Momordica charantia L. and Luffa acutangula L. scions grafted on Cucurbita moschata L. and Trichosathes cucumerina L. rootstocks during both seasons and there was non-significant difference between two seasons.